Efficacy of different protocols of ovulation synchronization and resynchronization in argentinian buffalo herds - Crudeli, Gustavo Ángel (2019)
Fil: Crudeli, Gustavo Ángel. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias; Argentina..